Correlation Between the COVID-19 Respiratory Triage Score and SARS-COV-2 PCR Test - Aldobyany, Ahmad; Touman, Abdelfattah; Ghaleb, Nabil; Alsaggaf, Rajaa; Murtaza, Noureen; Hamada, Adel; Alknawy, Moataz; Albanna, Amr S.; Alqurashi, Eid (Frontiers in Medicine, 2020)
Background COVID-19 clinical presentation is usually non-specific and include commonly encountered symptoms like fever, cough, nausea and vomiting. It has been reported that COVID-19 patients can potentially transmit the disease to others before developing symptoms. Thus, extensive surveillance and screening of individuals at risk of the disease is required to limit SARS-COV-2 spread. COVID-19 respiratory triage score has been used for patients screening. We aimed to determine its diagnostic performance characteristics, which have not been adequately studied before Methodology This is a retrospective observational study involving all patients screened for COVID-19 at a tertiary care facility. Patients were tested using nasopharyngeal swab for SARS-COV-2 PCR. The Saudi CDC COVID-19 respiratory triage score was measured for all subjects. The sensitivity, specificity, positive predictive value and negative predicted value of COVID-19 respiratory triage score were measured with reference to SARS-COV-2 PCR test. Multivariate regression analysis was done to identify factors that can predict positive SARS-COV-2 PCR test. Result A total of 1435 subjects were included. COVID-19 respiratory triage score provided a marginal diagnostic performance, with a receiver-operating characteristics (ROC) area under the curve value of 0.60 (95% CI: 0.57 – 0.64). A triage score of 5 provided the best cut-off value for the combined sensitivity and specificity. Clinical characteristics that independently predicted positive COVID-19 PCR test include male sex (adjusted OR: 1.47; p= 0.034), health care workers and their family members (adjusted OR: 1.99; 95%; p= 0.016), fever (adjusted OR: 2.98; p< 0.001), and moderate disease severity (adjusted OR: 5; p< 0.001). Conclusion The current COVID-19 respiratory triage score has marginal diagnostic performance characteristics. Its performance can improve by including additional predictors to the respiratory symptoms in order to avoid missing COVID-19 patients with atypical presentation and to limit unnecessary SARS-COV-2 PCR testing.